KEY ISSUES INFLUENCING THE MANAGEMENT OF RISKS IN THE AUSTRALIAN FITNESS INDUSTRY – COMBINING LEGAL PERSPECTIVES WITH INJURY PREVENTION APPROACHES. Issue 7 (11th March 2014) - Keyzer, P; Finch, CF; Norton, KI; Dietrich, J; Sekendiz, B.; Coyle, I
Abstract : Background: The Australian Fitness Industry Risk Management Project considers 1) How does Australian regulation currently control risk management in the fitness industry and thereby prevent adverse health outcomes and injury, and the legal liability associated with those risks? 2) What sustainable changes could be made to Australian regulation for more effective risk management in the health and fitness industry in order to prevent the risk of adverse health outcomes and injury, and the legal liability associated with those risks?. Objective: Develop new best practice benchmarks to improve safety in the fitness industry and reduce the risk of adverse health and injury outcomes. Setting: Australia-wide fitness facilities. Participants: 1178 respondents from Australian fitness facilities. 62% female. Mean age, 40 years. 46% self-employed or sole traders. 2% were part-time employees of a fitness facility. Interventions: Observational, ecological study. Based on nominal group technique applied within focus groups in four States of Australia, we developed a national survey that included 45×6-point Likert scale items that were factor analysed. The survey was administered online during May-June 2013 and promoted mainly through social media and direct e-marketing. Results: Focus group respondents reported (lack of) education and supervision, (poor) technique, (defective) equipment, (unsuitable) environment and overcrowding as principal issues, while also raising issues of scope of practice, defective pre-exercise screening, medical risks associated with de-conditioned clients, inappropriate nutritional advice, inadequacy of qualifications and unrealistic client expectations. The survey designed around these themes identified three key challenges for the fitness industry: management implementation & monitoring of safety policy; client training/education in exercise programmes; and maintenance, design & operation of the facility/equipment. Conclusion: The key challenges require legal and fitness setting specific solutions to address key risks. Ongoing management within the fitness industry will ensure these are appropriate and can be implemented.